Legal Protection for Parties in Online Sale and Purchase Agreement - Leriana, Helda; Djaja, Benny; Sudirman, Maman (Civiliza Publishing, 2025)
More and more people are taking advantage of the convenience offered by online shopping thanks to advances in information technology. Nevertheless, there are a number of legal issues lurking behind the convenience offered, including unclear rights and responsibilities of the parties, conflict resolution, and consumer protection from unsuitable or harmful products. The purpose of this study is to examine the strengths and weaknesses of the Indonesian legal system, evaluate the effectiveness of existing regulations, and determine the extent to which the parties to online sales and purchase agreements are legally protected. This study uses a qualitative normative juridical methodology, with information gathered from a review of laws, scientific articles, and other relevant legal documents. The results of the study show that the low level of public legal literacy and the absence of an efficient online dispute resolution process are 2 (two) areas where the laws governing consumer protection still have room for improvement. To build a secure and sustainable digital commerce ecosystem, existing legal protections for online transactions need to be optimized and legal education for consumers and business actors needs to be improved.